The Effect of Ethanol Concentration Variations on The Total Phenolic And Flavonoid Levels of Bauhinia purpurea L. Leaf Extract - Nurhasanah, Devika; Ulvia, Rengganis; Junita, Fina (Journal of Biotechnology and Natural Science, 2024)
Bauhinia purpurea L. is an ornamental plant that is not widely known or explored by the public, despite its significant antioxidant properties. Phenolic compounds and flavonoids, known for their antioxidant activity, can be extracted from the leaves through maceration with 70% ethanol and 96% ethanol. The difference in solvent polarity between these two ethanol concentrations affects the solubility of bioactive compounds. This study aimed to evaluate the effect of 70% and 96% ethanol concentrations Bauhinia purpurea L on the total phenolic and flavonoid levels in. An experimental method was employed, using Bauhinia purpurea L powder macerated with 70% and 96% ethanol, followed by evaporation at 40°C-50°C to obtain thick extracts. The extracts were subjected to organoleptic tests, phytochemical screening, Thin Layer Chromatography (TLC), and UV-Vis spectrophotometry. Total phenolic content was determined using gallic acid standards (mg GAE/g extract), while total flavonoid content was measured using quercetin standards (mg QE/g extract). The organoleptic test revealed that both the 70% and 96% ethanol extracts of Bauhinia purpurea L had a blackish-green color, thick consistency, distinctive odor, and bland taste. Phytochemical screening indicated the presence of phenolics, flavonoids, and saponins. The total phenolic content for the 70% ethanol extract was 14.644 ± 0.222 mg GAE/g, and the total flavonoid content was 25.519 ± 0.921 mg QE/g. The total phenolic content for the 96% ethanol extract was 7.176 ± 0.347 mg GAE/g, and the total flavonoid content was 11.208 ± 0.412 mg QE/g. These results indicate a significant difference between the use of 70% and 96% ethanol in extracting total phenolic and flavonoid content from Bauhinia purpurea L, with the 70% ethanol extract showing higher levels of both compounds.